Managed grazing and agroecological transformation in the Midwestern United States - Lowe, Erin B.; Fochesatto, Ana; Rissman, Adena R. (Frontiers in Sustainable Food Systems, 2023)
A growing number of intergovernmental agencies, policymakers, scholars, and farmers are calling to transform the dominant food system so that it better supports farmers, communities, and the environment. The goal of this paper is to identify which actions that support managed livestock grazing and graziers can also promote agroecological transformation in the Midwestern U.S. We conducted 128 semi-structured interviews and 3 participatory workshops with farmers, civil society, and agricultural industry professionals focused on visions for the future and actions that could support managed grazing. We then applied a political agroecology framework to assess the transformative potential of specific actions. Action categories with high transformative potential include addressing industry consolidation and inequities in the distribution of land and capital; providing social supports for farm owners and workers; and shifting the social norms that support the dominant food system. Specific actions within these categories include supporting cooperative models of farming, marketing, and resource-sharing; providing healthcare, living wages, and retirement to farmers; supporting farmer-to-farmer networks; modifying crop insurance and anti-trust legislation; addressing farmland access and consolidation; expanding public education on agroecology; and enacting policies that dismantle and repair colonial and racial violence. The workshops revealed that a disproportionate share of attention within the Midwest sustainable agriculture movement is currently focused on strategies that support sustainable farming practices such as education and conservation assistance but do little to address governance structures that maintain the power of the current agricultural system. While these efforts are important, workshop participants and interviewees concluded that more systemic change is needed to build a food system that works better for people, communities, and the environment.